Assessing the Quality, Utility, and Value of Case Formulation in the Offender Personality Disorder Pathway - VICTORIA WHEABLE (2021)
The Offender Personality Disorder Pathway (OPDP) was co-commissioned in 2011 by the National Offender Management Service (NOMS) and the National Health Service (NHS) to better manage high-risk offenders with personality disorder. To meet this aim, the OPDP provides offenders with a pathway of psychologically centred services, informed in part by an individualised forensic case formulation. Forensic case formulation is a process by which hypotheses are developed to explain the psychological origins of an offender’s presenting problems and difficulties, why and how these problems have been maintained over time, and how these problems may be effectively reduced in future. However, despite the centrality of forensic case formulation to the OPDP, its quality, utility, and value within this service is not well understood. To begin to remedy this, the four studies presented within this thesis were conducted to a) empirically investigate the necessary components of a ‘high-quality’ forensic case formulation, b) identify the potential benefits of completing forensic case formulation within the OPDP, and c) understand how forensic case formulation within the OPDP can be usefully improved to enhance any such benefits. Despite the disruption of COVID-19 on research proceedings, the conclusions of this research indicate that performing forensic case formulation within the OPDP does have a number of small-scale benefits, and that it is possible for these benefits to be further enhanced. These findings are expected to have important implications for practice within the OPDP and for the use of forensic case formulation in general. It is however strongly recommended that the research presented within this thesis be developed further to examine whether the small-scale benefits identified can indeed be enhanced to create larger positive outcomes, such as reductions in recidivism. A comprehensive plan for this further research is included.